2017
DOI: 10.1123/ssj.2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

‘Life in the Travelling Circus’: A Study of Loneliness, Work Stress, and Money Issues in Touring Professional Golf

Abstract: This article examines the effects of globalization on the well-being of migrant professional athletes. Interviews with 20 touring professional golfers reveal that players experience many of the personal problems -such as loneliness, isolation, low decision latitude, low social support, and effort-reward imbalance -which have been identified as "strong predictors of mental ill-health" (Leka & Jain, 2010, p. 65). Feelings of loneliness and isolation developed as players were regularly apart from family and frien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…This notion of cultural loneliness could persist even when people had good access to social networks. Studies of social loneliness in the employment context identified a lack of support and employment-related 'distancing' or isolation from others from a diverse range of employees including long-haul truck drivers [26], homeworkers [46], school principals [57,60,113], medical educators [96], professional golfers [40], and senior corporate managers [104], as well as family caregivers [45,98]. Homeworkers and family caregivers seem to be especially vulnerable.…”
Section: Social Lonelinessmentioning
confidence: 99%
“…This notion of cultural loneliness could persist even when people had good access to social networks. Studies of social loneliness in the employment context identified a lack of support and employment-related 'distancing' or isolation from others from a diverse range of employees including long-haul truck drivers [26], homeworkers [46], school principals [57,60,113], medical educators [96], professional golfers [40], and senior corporate managers [104], as well as family caregivers [45,98]. Homeworkers and family caregivers seem to be especially vulnerable.…”
Section: Social Lonelinessmentioning
confidence: 99%
“…Other articles discuss workplace loneliness in the context of organisations but do not define it directly (e.g. Chan and Qiu, 2011; Chou and Chang, 2016; Fry and Bloyce, 2017).…”
Section: Defining and Conceptualising Loneliness In The Workplacementioning
confidence: 99%
“…Previous research has overwhelmingly focused on men's football, which details an unpredictable workplace (McGillivray & McIntosh, 2006;Roderick, 2006). Professional sport is often glamorised as a care-free occupation with high economic rewards and a celebrity lifestyle (Fry & Bloyce, 2017). However, a career as a professional women's footballer is increasingly complex and characterised by its gendered precariousness (Culvin, 2020).…”
Section: The Precarious Work Of Professional Women Footballersmentioning
confidence: 99%